2017
DOI: 10.1590/1413-70542017412029416
|View full text |Cite
|
Sign up to set email alerts
|

Drought-induced alterations in the uptake of nitrogen, phosphorus and potassium, and the relation with drought tolerance in sugar cane

Abstract: Alterações induzidas pela seca na absorção de nitrogênio, fósforo e potássio, e as relações com a tolerância da cana-de-açúcar ao deficit hídrico July, 19, 2016 and approved in November 23, 2016 ABSTRACTAlthough there are evidences that the proper supply of mineral nutrients to plants relieves water stress, little is known on the approach of how the drought affects the absorption and accumulation of nutrients by distinct sugar cane genotypes, or in different parts of a same plant. Thus, the objective of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 12 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…These results show that when irrigation management is adopted with a fractional addition of water, the probability Table 3. Summary of analysis of variance and results of the comparison test of means for the evaluated variables of cantaloupe melon (variety Rock Hybrid Cantaloupe) subjected to different irrigation frequencies and substrate volumes ***, **, *, ns -Significant at p ≤ 0.001, 0.01, 0.05 and not significant, respectively, by F test; 1 Square-root-transformed data; DF -Degrees of freedom; CV -Coefficient of variation; Means followed by the same letter in the column did not differ significantly from each other by Tukey test, (p ≤ 0.001, 0.01 and 0.05) of occurrence of water deficit or loss of water by percolation decreases, thus the fractional addition of water allows the maintenance of micropores with sufficient water for the absorption of nutrients by the plants, because according to Silva et al (2017), it is evident that the movement of nutrients from the soil towards the root depends on the presence of water. The greater absorption of water and nutrients by the melon allows the plant to produce fruits of larger size and thicker pulp, since it is possible to produce a greater volume of photoassimilates.…”
Section: Resultsmentioning
confidence: 99%
“…These results show that when irrigation management is adopted with a fractional addition of water, the probability Table 3. Summary of analysis of variance and results of the comparison test of means for the evaluated variables of cantaloupe melon (variety Rock Hybrid Cantaloupe) subjected to different irrigation frequencies and substrate volumes ***, **, *, ns -Significant at p ≤ 0.001, 0.01, 0.05 and not significant, respectively, by F test; 1 Square-root-transformed data; DF -Degrees of freedom; CV -Coefficient of variation; Means followed by the same letter in the column did not differ significantly from each other by Tukey test, (p ≤ 0.001, 0.01 and 0.05) of occurrence of water deficit or loss of water by percolation decreases, thus the fractional addition of water allows the maintenance of micropores with sufficient water for the absorption of nutrients by the plants, because according to Silva et al (2017), it is evident that the movement of nutrients from the soil towards the root depends on the presence of water. The greater absorption of water and nutrients by the melon allows the plant to produce fruits of larger size and thicker pulp, since it is possible to produce a greater volume of photoassimilates.…”
Section: Resultsmentioning
confidence: 99%
“…Q50. Silva et al (2017) reported the uptake of nitrogen was reduced significantly under the effect of water stress. In this study, drought stress reduced TNU of all varieties, but not significantly.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, drought stress reduced TNU of all varieties, but not significantly. Water shortage might reduce dissolved nitrogen ability (in the form of urea which was applied just 10 days before plant subjected to water stress) which leads to reducing the amount of nitrogen uptake in Silva et al (2017)'s experiment. Meanwhile, in this study, the dissolved nitrogen was applied weekly even during water stress period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It does not require concentration processes and chemical attacks [9]; it may be ready for use (as in the present situation) and production costs are minimal (extraction and crushing costs when needed, will not exceed US$ 10 per ton) [2,4,10]. The technology of rock fertilizers is widely developed in countries such as Brazil, China and Australia [11][12][13][14][15][16]. In addition, it has been noted that regions covered by recent volcanic rocks are excellence areas of intensive farming.…”
Section: Introductionmentioning
confidence: 96%